REFORMA AGRARIA DAN PENGUATAN HAK: STRATEGI PENATAAN KEMBALI KEPEMILIKAN TANAH DAN PERLINDUNGAN HAK MASYARAKAT ADAT TERHADAP ANCAMAN INVESTASI DAN KORPORASI BESAR - Jackson Yumame (CV. ADIBA AISHA AMIRA, 2025)
This study discusses agrarian reform strategies as efforts to restructure land ownership and strengthen the rights of indigenous peoples in the face of threats from large investments and corporations in Indonesia. Through a literature review, the study examines policies, regulations, and practices related to land redistribution, asset legalisation, and the protection of indigenous peoples' customary lands. The results of the study show that agrarian reform has great potential to reduce land ownership inequality and strengthen the position of indigenous peoples if implemented with cross-sector coordination and strong political commitment. However, threats from large corporations seeking land expansion continue to pose a serious challenge, making the protection of indigenous peoples' rights through legal recognition, the principle of free, prior and informed consent (FPIC), and socio-economic empowerment very important. This study provides strategic recommendations so that agrarian reform and the protection of indigenous peoples' rights can work synergistically to achieve social justice and sustainable development.